2015
DOI: 10.1111/gfs.12196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional salt placement and strategically placed mineral mix supplements on cattle distribution in the Western Italian Alps

Abstract: Effects of traditional salt placement (TS) and strategically placed mineral mix supplements (MMS) on cattle distribution were compared in the Italian Alps. Salt was placed within flat and herbaceous sites following the traditional method of farmers, whereas MMS blocks were placed on steep and shrub-encroached sites within three large pastures (44 ha on average). Each TS and MMS site was paired with a control site and eleven cows were tracked with GPS collars. Within 10 and 50 m of TS and MMS, treatment sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…The role of grazing in preserving and improving grassland ecosystems has been widely studied (Adler, Raff, & Laurenroth, ; Collins, Knapp, Briggs, Blair, & Steinauer, ; Li et al., ; Sebastià, De Bello, Puig, & Taull, ). Livestock management influences plant species composition (Olff & Ritchie, ), nutrient redistribution (Dai, ; Gaujour, Amiaud, Mignolet, & Plantureux, ; Lonati, Probo, Gorlier, & Lombardi, ; Malo & Suarez, ), biomass removal (Borer et al., ) and soil and plant species cover through grazing, trampling, excreta deposition and seed transportation (Pittarello, Probo, Lonati, Bailey, & Lombardi, ; Pittarello, Probo, Lonati, & Lombardi, ; Probo, Pittarello, Lonati, & Lombardi, ). Hence, it can modify intra‐specific and inter‐specific competition dynamics among plant species, often favouring meso‐eutrophic species dominance within regularly grazed grasslands (Nervo et al., ; Niu, He, & Lechowicz, ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of grazing in preserving and improving grassland ecosystems has been widely studied (Adler, Raff, & Laurenroth, ; Collins, Knapp, Briggs, Blair, & Steinauer, ; Li et al., ; Sebastià, De Bello, Puig, & Taull, ). Livestock management influences plant species composition (Olff & Ritchie, ), nutrient redistribution (Dai, ; Gaujour, Amiaud, Mignolet, & Plantureux, ; Lonati, Probo, Gorlier, & Lombardi, ; Malo & Suarez, ), biomass removal (Borer et al., ) and soil and plant species cover through grazing, trampling, excreta deposition and seed transportation (Pittarello, Probo, Lonati, Bailey, & Lombardi, ; Pittarello, Probo, Lonati, & Lombardi, ; Probo, Pittarello, Lonati, & Lombardi, ). Hence, it can modify intra‐specific and inter‐specific competition dynamics among plant species, often favouring meso‐eutrophic species dominance within regularly grazed grasslands (Nervo et al., ; Niu, He, & Lechowicz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within permanent mountain pastures, optimal livestock pressure for biodiversity conservation can be achieved by using specific pastoral practices (Pittarello et al, 2016a;Pittarello et al, 2016b) and/or by adjusting the number of grazing animals, the area available for grazing, the grazing schedule and system (e.g. rotational or continuous grazing; Farruggia et al, 2014;Probo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Grazing Management Plan can account for the integration of RGS with supplementary pastoral practices (i.e. strategic placement of drinking troughs and mineral mix supplements, arrangement of temporary night camp areas, etc..), which can additionally improve grazing distribution, botanical composition, vegetation structure, and forage quality (Probo et al 2013;Pittarello et al 2016a;Probo et al 2016). A research conducted in the same study area (Perotti et al 2018) demonstrated that RGS increased the average soil nutrient content of the whole pasture over a five-year span.…”
Section: Discussionmentioning
confidence: 99%